Literacy as Resistance: Critical Framing for Promoting Ecological Awareness - Ahmad Iklil Saifulloh; Pratiwi Retnaningdyah; Ali Mustofa; Suhartono Suhartono (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
The persistent use of traditional teaching methods is often underrated and dismissed as outdated in Indonesia, but this does not mean it should be abandoned entirely. By preserving traditional practices and combining with multimodality, this study explores the transformative potential of Multimodality, focusing on the Critical Framing (CF) of the Multiliteracy Pedagogy Frameworks (MPF) under the New London Group (NLG), and Transformative of Eco-Linguistics and Eco-Cultural Awareness. Focusing on East Java, Indonesia, the research employs a transformative case study involving a Ph.D. student serving as a lecturer and language learners in a green university. CF emerges as a groundbreaking approach to foster students' critical thinking, cultural integration, and learning evolution. The findings reveal CF's effectiveness in enabling essential analysis of Film Promotion and exploring identity, ideology, and values. It introduces gradually dismantling scaffolded instruction in diverse learning contexts. CF promotes the new multimodal designs to realize quality education, local tourism, and facilitate eco-cultural wisdom.